2018
DOI: 10.1016/j.actbio.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

A bio-based pro-antimicrobial polymer network via degradable acetal linkages

Abstract: With the increasing number of patients prescribed immunosuppressants coupled with the rise in antibiotic resistance - life-threatening microbial infections are a looming global threat. With limited success within the antibiotic pipeline, nature-based essential oils (EOs) are being investigated for their multimodal effectiveness against microbes. Despite the promising potential of EOs, difficulties in their encapsulation, limited water solubility, and high volatility limit their use. Various studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…1A). However, application of the thiol-catalyzed process to acyclic benzylidene acetals, such as those employed as building blocks for our previous work, [15][16][17] would result in cleavage of the acetal to the benzoate ester and alkyl group 22 (Fig. 1B) -a process that we postulated could lead to polymer network destruction.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…1A). However, application of the thiol-catalyzed process to acyclic benzylidene acetals, such as those employed as building blocks for our previous work, [15][16][17] would result in cleavage of the acetal to the benzoate ester and alkyl group 22 (Fig. 1B) -a process that we postulated could lead to polymer network destruction.…”
mentioning
confidence: 89%
“…Sulfur-centered radicals are ubiquitous in many chemical and biological processes 1 and have found broad utility in synthetic polymer chemistry due to their facile formation and inherent reactivity. 2,3 Due to the relatively weak S-H bond (bond dissociation energy 79-87 kcal/mol), 4 thiyl radicals are readily generated by hydrogen atom abstraction of thiols via thermal or photochemical initiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Using this strategy, the antimicrobial agent p-anisaldehyde (pA) was entrapped in a polymeric mesh that was capable of controlled release under acidic conditions. When released it was observed that the antimicrobial activity of the pA was retained and resulted in significantly improved inhibition of MRSA compared to free drug controls with minimal toxicity observed [ 177 ]. However, it should be noted again, the potential for additional regulatory hurdles that may be associated with chemically binding the active drug to the delivery vector.…”
Section: Nanoparticle Delivery Of Antibiotics “Old Drugs New Tricmentioning
confidence: 99%